The Hematopoietic Cell Transplant Pharmacist: A Call to Action - Amber Clemmons (MDPI AG, 2020)
Recently, the required training and credentials for as well as the various roles of the hematopoietic cell transplant (HCT) pharmacist have been endorsed by the leading organizations in cellular therapy, the American Society of Transplant and Cellular Therapy and the European Society of Blood and Bone Marrow Transplantation. While these documents establish the roles a HCT pharmacist can fulfill within the multi-disciplinary team, few reports have evaluated the impact of the HCT pharmacist on clinical, financial, or quality outcomes. Further, a paucity of information has been reported on types of practice models, such as the use of collaborative practice agreements, or described effective methods to overcome the barriers to the increased utilization of HCT pharmacists. Herein, a brief summary of available information is provided to aid readers in understanding the state of the science for pharmacists practicing in this specialty with the goal to stimulate further research to justify the roles of HCT pharmacists and the correlation of such research to various outcome measures. Practitioners are encouraged to build upon this existing knowledge to create the novel integration and elevation of pharmacy practice to improve outcomes for patients, providers, and payors.